Alternative modification by grafting in bamboo cellulose nanofibrils: A potential option to improve compatibility and tunable surface energy in bionanocomposites - Rodriguez Ramirez, Carlos Alejandro (2022)
Chemical modification in surface of cellulose nanofibrils CNFs (20 nm) from an endemic and non-significant value-added, Argentine bamboo, was developed. The modification in the CNFs was carried out with three simple routes using a low molecular weight polylactic acid synthesized in our laboratory (PLA1). The first step comprises of protection of the hydroxyl groups of PLA1 through a benzoylation (PLA1Bz). The next step consisted of the activation of carboxyl groups using thionyl chloride and the last reaction was the grafting of the modified PLA onto the CNFs (PLA1Bz-g-CNF). The covalently functionalization is confirmed by spectroscopically techniques as well as PLA1Bz-g-CNFs were characterized by thermal analyses. The PLA1Bz-g-CNFs were taken up such as nanocharges to improve properties of compatibilization and changing surface properties in films based on PLA. The comparison between the films with PLA1Bz-g-CNFs with respect to the physic mixture of the components (PLA1Bz/CNF), shows an improvement in the thermal, mechanical, and surface properties of the material, particularly when 5% of PLA1Bz-g-CNFs was added. The dispersive (γS D) component of film is increased in 36.1 mN/m respect to 29.3 mN/m from the films obtained with the physic mixture nanofibrils without modification and a plasticizing effect was noticed in the final material.